Usage of foreign criminal judgement in Polish civil proceedings - Wasylkowska-Michór, Magdalena Anna (The Opole Studies in Administration and Law, 2021)
The main aim of this paper is to identify the most important problems that arise when interpreting Article 11 of the Polish Code of Civil Procedure, which provides, in civil proceedings, the conditions of application of a criminal judgment, including a foreign criminal one. Therefore, at the very beginning of the paper, the judgment of the Supreme Court of 27 March 2013 in the case ref. V CSK 185/12 is presented, as the starting point for further considerations. This judgment states that the above-mentioned Article 11 also applies to a final judgment issued in criminal proceedings by a court of a European Union country. Further in the paper, the author presents doubts concerning the interpretation of Article 11, which may also arise when a foreign criminal judgement is involved. They relate mainly to the notion of a conviction and the nature, and limits of binding a civil court with a criminal judgement.